Peningkatan Profesionalisme Guru IPS Melakukan Penelitian Tindakan Kelas Melalui Supervisi Akademik Di SMP Binaan Kota Lhokseumawe Tahun 2021 - Muhidin (Journal of Technology and Literacy in Education, 2022)
This study aims to determine the increase in the professionalism of social studies teachers in conducting classroom action research through the application of academic supervision at SMPs assisted by Lhokseumawe City in 2021. This research was carried out at SMPs assisted by researchers in Lhokseumawe City in odd semesters in 2021. 3 months, starting from August to October 2021. The research subjects were teachers assisted by researchers who were at SMP Negeri 4 Lhokseumawe, SMP Negeri 11 Lhokseumawe, SMP Negeri 13 Lhokseumawe, SMP Negeri 15 Lhokseumawe, SMP Negeri 6 Lhokseumawe, SMP Swasta Islam Pase and SMPS Al Quran Ar Raudah with a total of 15 teachers. The research conducted was School Action Research (PTS) which was conducted in two cycles. Each cycle consists of the planning stage, the action implementation stage, the observation stage and the reflection stage. Research data collection techniques obtained from the results of observations. The data analysis technique used in this study is descriptive qualitative using a percentage formula. The results of the study showed that in cycle I only 5 teachers had achieved research success indicators with good criteria with an overall average of 76.09%. Whereas in cycle II all teachers have achieved indicators of research success. As many as 4 teachers got very good criteria and 11 teachers got good criteria, with an overall average score of 88.53%. Experienced an increase of 12.44% from cycle I. So it can be concluded that through academic supervision can increase the professionalism of Social Sciences teachers conducting classroom action research at SMPs assisted by Lhokseumawe City in 2021.